The Mystical Ideas In The "West-East Office" Are Translated By Sadriddin Salim Bukhari - M.M. Mahmudova (Indonesian Journal of Innovation Studies, 2022)
The article tells about the skill of Sadriddin Salim Bukhari, translator, versatile writer, mystic, poet, who occupies a unique place in the Uzbek translation, in the translation of mystical ideas in the "West-Eastern Divan".